PENGOLAHAN AIR LIMBAH INDUSTRI PLASTICIZER DENGAN PENAMBAHAN OKSIDATOR KUAT - Unggul Baskoro (Purifikasi, 2008)
This research was aimed to analyze the effect of strong oxidator addition for COD and isopropanol removals in plasticizer wastewater. This research used wastewater from the inlet and outlet of DV-03 in PT Petronika Gresik. Strong oxidators were added into the reactor with a coagulation rate of 100 rpm for 10 minutes. The flocculation mixing rate was 40 rpm for 60 minutes. The wastewater samples were collected within 1 hour and 24 hours after the mixing process for COD and isopropanol measurements. The results showed that the COD removal was 46% and that of for isopropanol was 82% with the addition of H2O2. The addition of fenton reagent (Fe2+ and H2O2 1:4) at dose of 40 g/L removed 96% of COD and 93% of isopropanol in the outlet DV-03 wastewater samples.